2003
DOI: 10.4049/jimmunol.171.5.2384
|View full text |Cite
|
Sign up to set email alerts
|

Cholera Toxin Promotes the Induction of Regulatory T Cells Specific for Bystander Antigens by Modulating Dendritic Cell Activation

Abstract: It has previously been reported that cholera toxin (CT) is a potent mucosal adjuvant that enhances Th2 or mixed Th1/Th2 type responses to coadministered foreign Ag. Here we demonstrate that CT also promotes the generation of regulatory T (Tr) cells against bystander Ag. Parenteral immunization of mice with Ag in the presence of CT induced T cells that secreted high levels of IL-4 and IL-10 and lower levels of IL-5 and IFN-γ. Ag-specific CD4+ T cell lines and clones generated from these mice had cytokine profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
108
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 34 publications
(43 reference statements)
10
108
1
Order By: Relevance
“…This suggests that a physical association between the two modulators (as in the case of CyaA and LPS) is not essential for the synergy, but possibly binding to two distinct receptors is involved. This hypothesis is supported by previous studies showing synergy between TLR and other signaling pathways (24,25). NA-CyaA and A-CyaA also had similar effects on DC maturation, up-regulating CD80 expression, while down-regulating CD40 and ICAM-1 expression.…”
Section: Discussionsupporting
confidence: 77%
“…This suggests that a physical association between the two modulators (as in the case of CyaA and LPS) is not essential for the synergy, but possibly binding to two distinct receptors is involved. This hypothesis is supported by previous studies showing synergy between TLR and other signaling pathways (24,25). NA-CyaA and A-CyaA also had similar effects on DC maturation, up-regulating CD80 expression, while down-regulating CD40 and ICAM-1 expression.…”
Section: Discussionsupporting
confidence: 77%
“…This observation led us to analyze whether M proteins may induce a Tr1 phenotype in human CD4 ϩ T cells. Although several pathogenic microorganisms, including Bordetella pertussis (19) and Vibrio cholerae (20), have recently been shown to induce Tregs by interfering with dendritic cell maturation (19 -21), our data indicate that S. pyogenes interact with CD46 on human CD4 ϩ T cells to generate directly cells with a Tr1-like regulatory phenotype.…”
Section: Induction Of a Regulatory Phenotype In Human Cd4 ؉ T Cells Bmentioning
confidence: 77%
“…The mechanism reported for B. pertussis (19) and V. cholerae (20) centers on the inhibition of dendritic cell maturation, which indirectly causes the induction of Tregs. A similar mechanism might operate for the other pathogens that cause immunosuppression by inducing IL-10 (33-37).…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of CT can in parallel with its adjuvant action prevent induction of oral tolerance to a coadministered Ag (17)(18)(19)33), although CT has also been reported (34) to promote the induction of T reg (Tr1 cells) in vitro. In this study, we found that coadministration of even very small amounts of CT together with the OVA/CTB conjugate effectively prevented the induction of CD25 ϩ CD4 ϩ suppressor T cells.…”
Section: Discussionmentioning
confidence: 99%